KEMAMPUAN PENALARAN ILMIAH SISWA KELAS XI SMAN DI BANYUWANGI KOTA MATERI SUHU DAN KALOR - Elok Yieldsihas Faiqoh; yushardi yushardi; Alex Harijanto (Universitas Jember, 2020)
Scientific reasoning ability is important to have for students to understand the concept of physics and have a good mathematical reasoning ability. The scientific reasoning ability itself is the ability of a person to use his or her reasoning in resolving a problem by coming up with facts or tangible evidence, so that the conclusion can be drawn. The research was conducted with a view to analyzing the scientific reasoning ability of high school students in Banyuwangi city on temperature and heat material. The study used a research instrument in the form of a multiple-choice scientific reasoning ability test based on LCTSR. This type of research is descriptive research. The results of this research include the percentage of test result scientific reasoning ability of students in Banyuwangi city in the proportional reasoning is 60.51%, in variable control of 58.17%, at a probability reasoning of 49.87%, on The hypothetical-deductive reasoning is 47.4%, on the reasoning correlation of 20.53%, and the reasoning on conservation is 37.22%. The largest percentage is proportional reasoning, while the smallest is a correlation reasoning. Then it can be said that high school students in Banyuwangi City have the best scientific reasoning ability on the proportional reasoning pattern and the ability of scientific reasoning which is lacking in the pattern of reasoning the correlation.